1993
DOI: 10.1099/0022-1317-74-11-2525
|View full text |Cite
|
Sign up to set email alerts
|

A 29K envelope glycoprotein of equine arteritis virus expresses neutralization determinants recognized by murine monoclonal antibodies

Abstract: A panel of six neutralizing murine monoclonal antibodies (MAbs) to equine arteritis virus (EAV) was produced. The MAbs were characterized by Western immunoblotting assay and competitive ELISA. The six MAbs identify a single neutralization site on a 29K envelope glycoprotein. Deglycosylation of viral proteins prior to immunoblotting showed that the 29K protein is the glycosylated form of a 20K protein. Equine anti-EAV serum also strongly bound the 29K glycoprotein, as well as an unglycosylated protein of 17K. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 20 publications
1
59
0
1
Order By: Relevance
“…Furthermore, a number of sera that had significant titers of neutralizing antibody as determined by SN test did not bind the G L protein in the immunoblotting assay despite the fact that the G L protein expresses the known neutralization determinants of EAV. [1][2][3]8,17,21 However, the immunoblotting assay described here is very useful in confirming the protein specificity of antibodies in horse serum, and the data strongly suggest that the M protein should be targeted for future development of an improved diagnostic ELISA for serologic detection of EAV infection of horses. Furthermore, the immunoblotting assay has potential diagnostic utility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a number of sera that had significant titers of neutralizing antibody as determined by SN test did not bind the G L protein in the immunoblotting assay despite the fact that the G L protein expresses the known neutralization determinants of EAV. [1][2][3]8,17,21 However, the immunoblotting assay described here is very useful in confirming the protein specificity of antibodies in horse serum, and the data strongly suggest that the M protein should be targeted for future development of an improved diagnostic ELISA for serologic detection of EAV infection of horses. Furthermore, the immunoblotting assay has potential diagnostic utility.…”
Section: Discussionmentioning
confidence: 99%
“…The production and characterization of MAbs to the G L (MAb 6D10) and N (MAb 3E2) proteins of EAV has been previously described. 1,3,35 Polyclonal rabbit antisera to the G S and M proteins of EAV were prepared by immunization of rabbits with synthetic peptides specific for the amino acid sequence of the extreme carboxy terminus of each protein (G S : NH 2 -Cys-Pro-Ser-Arg-Arg-Thr-Ser-Ser-Gly-Thr-LeuPro-Arg-Arg-Lys-Ile-Leu-COOH; M: NH 2 -Tyr-Ala-GlyArg-Leu-Phe-Ser-Lys-Arg-Thr-Ala-Ala-Thr-Ala-Tyr-LysLeu-Gln-COOH). 13 Rabbits initially were immunized by subcutaneous inoculation of 10 mg of peptide conjugated to keyhole limpet hemocyanin in adjuvant j and subsequently boosted 3 times at 3-wk intervals by subcutaneous inoculation of the peptide in Freund's complete or incomplete adjuvant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A live attenuated vaccine (Doll 0001-3134 © 1995 SGM E. D. Chirnside and others et al, 1968;Harry & McCollum, 1981;Timoney et al, 1988) and inactivated whole virus vaccines (McCollum, 1986;Fukunaga et al, 1990Fukunaga et al, , 1992 induce VN antibody responses in horses. Western blotting and competition ELISA data (Balasuriya et al, 1993) indicate that strongly neutralizing monoclonal antibodies recognize a single epitope on a 29 kDa EAV protein which is likely to correspond to G L. Recently Deregt et al (1994) demonstrated that from a panel of monoclonal antibodies to the EAV N and GT, proteins all of the neutralizing antibodies recognized G~. Competitive binding assays revealed that they all bound to the same or to closely adjacent sites on the GL protein.…”
Section: Introductionmentioning
confidence: 99%